PERAN SIKAP DALAM MEMEDIASI PENGARUH GAYA HIDUP TERHADAP MINAT BELI SMARTPHONE IPHONE DI KOTA DENPASAR - Febryantha Mantala, I Putu; Suasana, I Gst. A. Kt. Gd. (E-Jurnal Manajemen, 2019)
The purpose of this study was to determine the role of attitudes in mediating the influence of lifestyle on buying interest. This research was conducted in Denpasar City to determine the role of attitudes in mediating the influence of lifestyle on the interest in buying Iphone smartphones. The number of samples taken was 100 respondents. The number of samples was set as many as 100 respondents using purposive sampling technique. Data collection was carried out by distributing questionnaires and data was measured using a 5 likert scale. Data were analyzed using path analysis and sobel test techniques. The results of the analysis showed that lifestyle had a significant effect on buying interest, lifestyle had a significant effect on attitudes, attitude had a significant effect on buying interest, and this study also proved that lifestyle had a significant effect on purchase intention mediated by attitudes Keywords: purchase intention, attitude, and lifestyle